1.1k views
16 votes
CLICK HERE IF YOU HAVE BIG FEET

Using the function g( x) = -2 x – 11, calculate g(-3).

User Raheel
by
5.0k points

1 Answer

8 votes

════════ ∘◦❁◦∘ ════════

Answer = -5

════════════════════

Known

g(x) = -2x - 11

════════════════════

Question

g(-3) = ..?

════════════════════

Way to do

#since x inside (x) change into (-3) then it means that you only need to change x into -3

g(-3) = -2(-3) - 11

g(-3) = 6 - 11

g(-3) = -5

════════════════════

User Mustapha GANGA
by
4.3k points